AgriTech4Kenya Innovation Challenge 2024: Bootcamp Highlight - CGIAR Accelerate for Impact Platform (2025)
As part of the AgriTech4Kenya Innovation Challenge, 25 selected teams converged in Limuru, Kenya, for a dynamic and interactive Bootcamp experience, from November 25th to 29th, 2024. This intensive four-day event provided participants with tailored technical mentorship, business strategy sessions, a field visit, and invaluable networking opportunities.